A cross-sector review on the use of value stream mapping - Shou, Wenchi; Wang, Jun; Wu, Peng; Wang, Xiangyu; Chong, Heap Yih (Taylor and Francis, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Value Stream Mapping (VSM) has become a popular method for lean thinking and implementation in recent years. Previous reviews related to VSM are limited to individual sectors due to varied research objectives. The lack of studies which focus on cross-sector review of VSM studies is impeding the implementation of VSM by both lean researchers and practitioners. The paper aims to determine the-state-of-the-art development of VSM in five sectors, including manufacturing, health care, construction, product development and service sectors. A total of 131 journal articles are reviewed and analysed from the period of 1999â€“12/2016. The analysis covers the complete implementation cycle of VSM, including metrics for current state map, improvement techniques for future state map, benefits and achievements of VSM application, and critical success factors for VSM implementation. Cross-sector comparisons and investigations are conducted to understand the differences of VSM implementations in various sectors to facilitate VSM development and increase the number of successful VSM implementation. The results suggest that understanding value and waste in a diverse value stream environment and ensuring the suitability and usability of traditional lean metrics/techniques within the different flow settings are central to the VSM development.